Detecting change in psychiatric functioning in clinical trials for cocaine use disorder: sensitivity of the Addiction Severity Index and Brief Symptom Inventory. (1st November 2021) - Kiluk, Brian D.; Roos, Corey R.; Aslan, Mihaela; Gueorguieva, Ralitza; Nich, Charla; Babuscio, Theresa A.; Carroll, Kathleen M.
Abstract: Background: Assessment instruments commonly used in clinical trials to measure functional outcomes in substance users may lack sensitivity to detect change during treatment, potentially limiting findings regarding benefits of reduced drug use. This study evaluated the sensitivity of the Addiction Severity Index (ASI) to detect change in psychiatric functioning among cocaine users. Methods: Data were pooled across five clinical trials for cocaine use disorder (N = 492) that included a 12-week treatment period and 6-month follow-up. Within-person cohen's d′ was used to evaluate effect size of change on the Psychiatric Composite Score of the ASI (ASI-Psych) and Global Severity Index (GSI) of the Brief Symptom Inventory, as well as cocaine use. Results: Effect sizes were larger for GSI than ASI-Psych from baseline to week 12 (GSI d′ = 0.59; ASI-Psych d′ = 0.16), and 6-month follow-up (GSI d′ = 0.48; ASI-Psych d′ = 0.10). For those with non-zero ASI-Psych at baseline (n = 252), medium effect sizes were found over the 12-week period (d′ = 0.53) and 6-month follow-up (d′ = 0.47). Effect sizes for change in days of cocaine use were most similar to GSI in either sample. Conclusions: The ASI Psychiatric Composite Score may have limited sensitivity to detect change in psychiatric functioning among clinical trial participants who reduce cocaine use. It may be useful for detecting change amongst those reporting some psychiatric problems at the start of treatment. Future research should consider an instrument's sensitivity to change when assessing the potential functional benefits of reducing cocaine use. Highlights: This study evaluated the effect size of change in psychiatric functioning. Cocaine users had limited change on ASI psychiatric domain during clinical trial. The Global Severity Index (GSI) from BSI showed medium effect size of change. Effect sizes for change in days of cocaine use were most similar to GSI. Assessing benefits of reduced cocaine use should consider sensitivity to change.